Extraction and Analytical Study of Semecarpus Anacardium L. Seed Oil (International Journal of Ayurveda and Pharma Research, 2024)
Bhallataka, also known as the marking nut or dhobi nut, is a potent ingredient in Ayurvedic medicine. Despite its irritant nature, it's been used for centuries to treat a myriad of diseases. Its oil, extracted using the Patala Yantra, is a key formulation in Ayurvedic pharmaceutics. Ayurveda, the ancient Indian system of medicine, is gaining global recognition for its holistic and natural approach to health. A significant part of Ayurvedic treatments are plant-based, ranging from raw plant materials to refined extracts. One such plant is Semecarpus anacardium Linn, the botanical source of Bhallataka. The plant is being traditionally used by the ancient healers in clinical practice. Apart from the clinical uses the plant was also used for marking clothes, as hair dyes and in many non-therapeutic uses as well. Bhallataka is a plant which holds much significance in Siddha and Unani system of medicine. Various studies have been conducted to understand its physical and chemical nature of the plant, in order to understand its use in therapeutic purposes. Chemical and phytochemical analysis of Bhallataka nut reveals a treasure trove of bioactive compounds- biflavonoids, phenolic compounds, bhilawanols, minerals, vitamins, and amino acids. These compounds make Bhallataka effective against various diseases like arthritis, tumors, and infections. The oil of Bhallataka, extracted using the Patala Yantra method, is particularly noteworthy. This oil is an integral part of Ayurvedic pharmaceutics, and its application is referenced in various ancient texts.